IXODES TICKS AS VECTORS OF TICK-BORNE INFECTIONS IN THE SOUTH OF PRIMORSKY KRAI (KHASANSKY DISTRICT) - V. A. Lubova; E. L. Bondarenko; G. N. Leonova (Acta Biomedica Scientifica, 2018)
The Khasan district, located in the south of the Primorsky Krai, borders with the Democratic People’s Republic of Korea (DPRK) and  the People’s Republic of China (PRC). This determines the special  importance in terms of epizootological observations of the causative  agents of vector-borne tick infections. To date, such studies have not  been carried out in the Khasan district.Aims: to show infections of ixodid ticks in the south of Primorsky Krai (in the Khasansky District), causative agents of viral and bacterial tick-borne infections.Materials and methods. During the period of 2017, 387 specimens of ixodid ticks were collected from the vegetation. The study of collected ticks was carried out using the real-time polymerase chain reaction method.Results. RNA of the TBE virus was detected in 1.1 %, Borrelia burgdorferi sensu lato DNA in 12.5 %, Borrelia miyamotoi DNA in 0.6 %, Anaplasma phagocytophillum DNA in 4 %, Ehrlichia chaffeensis /  Ehrlichia muris DNA in 1.7 %. In 8 %, rickettsia DNA was detected,  of which Rickettsia heilongjiangensis in 12 cases. Seven cases of  mixed infection of various species of ticks with two pathogens were detected.Conclusions. The data obtained suggest that the pathogens of infections transmitted by ixodid ticks can circulate not only  throughout the border area of the south of the Primorsky Krai  (Khasansky District) but also in the adjacent territories of the PRC and DPRK.